Shared carrier vertical network transformation algorithm in heterogeneous wireless networks - Liang ZHAO; Liang JIN; Kai-zhi HUANG; Mei-yue YANG (Tongxin xuebao)
In order to enhance the spectrum efficiency in heterogeneous wireless networks,the idea of dynamic spectrum allocation (DSA) used in cognitive radio was introduced into the heterogeneous wireless networks,the idea of vertical handoff for multi-mode mobile users was introduced into the base station side,thereafter,the shared carrier vertical network transformation (SCVNT) algorithm in heterogeneous wireless networks was proposed.The theoretical analysis and simulation results show that SCVNT algorithm can effectively enhance the total channel efficiency in heterogeneous wireless networks,improve fairness in resource allocation,and will be able to achieve smooth upgrade,which is of a relatively high application value.